History Has Its Eyes on You - Nordlund, Izabel (2020)
This study aims to understand some of the complexities of the Sami identity amongst young Sami women in Norrbotten County, Sweden. The Sami people are the only indigenous people living in the European Union and as many indigenous people around the globe, they are facing issues such as struggles over land rights, health issues and fragmented identities. The point of departure for this research is the settlement of the Girjas case, an end to a ten-year struggle about the authority over the fishing and hunting rights in the area between the Girjas Sami village and the Swedish Government. The Girjas case has given rise to a debate about indigenous rights and the Sami identity. The purpose of this thesis is to explore the complexity of the Sami identity to understand the perception of who is considered to be a genuine Sami today. To do so, I have interviewed eight young Sami women. To be able to understand their stories, and turning their words into a wider context, four main theoretical concepts have been used; identity, gender, intersectionality and heritage. The stories of the participants show that the Sami identity is perceived in many ways; it can be born out of upbringing, heritage and way of life, and not necessarily by ancestors only. Typical cultural carriers or symbols can confirm the Sami identity, but the participants mean that those are not a must. Different Sami identities are clashing with the created stereotypical image of who the genuine Sami is. This research shows that the Girjas case unite the Sami women in this thesis, regardless of their backgrounds or how they perceive their Sami identity. From the interviews, it appears that participants share a narrative of the importance of passing on the Sami heritage, never leaving the future generations with insecurity about their Sami identity. To understand the complex Sami identity, greater knowledge about Sami people and their history must be spread. By acknowledging that the Sami identity is not homogenous, further polarisation within the Sami ...